Oud neg.nr. 74684-74695. 'Vormingscentrum "De Wanne" Veenendaal, avond met W.S.W.-jongeren' - Haas, Joh. de
Oud neg.nr. 74684-74695. 'Vormingscentrum "De Wanne" Veenendaal, avond met W.S.W.-jongeren'.